2021
DOI: 10.3390/ijerph18137185
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life in High School Students: Proposals for Improving the Self-Concept in Physical Education

Abstract: Adolescence is a critical period for the acquisition of health-related behaviors that will transcend later psychological well-being in adulthood. The present study presents a theoretical model whose objective is to analyze how physical activity predicts an adequate quality of life through self-concept and subjective happiness among adolescents. A total of 452 students aged 12 to 15 (M = 13.8; SD = 0.77) from four Compulsory Secondary Education institutes of the Autonomous Community of Extremadura participated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…Moreover, results showed a direct relationship between physical activity and HRQoL. This relationship has been found in previous studies [ 54 ], where a higher level of physical activity was associated with an increased HRQoL [ 4 ]. Furthermore, a previous study reported a dose–response association between moderate to vigorous physical activity and HRQoL, where an increase in physical activity was associated with additional HRQoL benefits [ 55 ].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, results showed a direct relationship between physical activity and HRQoL. This relationship has been found in previous studies [ 54 ], where a higher level of physical activity was associated with an increased HRQoL [ 4 ]. Furthermore, a previous study reported a dose–response association between moderate to vigorous physical activity and HRQoL, where an increase in physical activity was associated with additional HRQoL benefits [ 55 ].…”
Section: Discussionsupporting
confidence: 84%
“…Physical activity, sedentary behavior, and body weight status among adolescents are important issues because these factors are associated with their health-"a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity" [32]. A previous study showed that physical activity could affect the quality of life of students aged 12 to 15 years old through self-concept and subjective happiness [33]. Based on the findings of a multivariate analysis, physical activity was also proven to be one of the significant factors positively associated with overall health-related quality of life [34].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a systematic review with a meta-analysis reported that PA interventions were linked to higher selfconcept in children and adolescents; the authors therefore indicated that PA at school should be increased to promote psychological well-being [74]. In addition, a theoretical model showed that PA mediated by self-concept predicted a better perception of quality of life in schoolchildren [75]. Babic et al [8] found that PA was positively related to PSC in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%